The Influence of Gender and Sexism on the Recommendation of Certificate Programs and Consumer Autonomy in Vocational Rehabilitation. - Sprong, Matthew E.; Currier, Kayla; Cerrito, Brianna; Buono, Frank D.; Hollender, Heaven (Journal of Rehabilitation)
Previous research has indicated that female vocational rehabilitation consumers are more likely to be placed with a lower starting wage (average of $4,360), and receive less on-the-job training, job readiness training, job search assistance, and job placement assistance. The purpose of the study was to evaluate how rehabilitation professionals recommend certificate and proficiency certificate programs when the consumer chooses a program that is not perceived as gender appropriate. Vocational Rehabilitation Professionals' (N = 348) were randomly assigned to 1 of 6 conditions where the rehabilitation goal and certificate program (i.e., receptionist and general office clerk, computer information systems) and gender of the hypothetical client (i.e., male, female, no gender disclosed) were manipulated. Findings revealed no significant differences between the male and female consumer in their pursuit of the female-dominated certificate program (i.e., receptionist and office clerk), and no significant gender differences when the consumer was pursuing the male-dominated certificate program (i.e., computer information systems). However, findings revealed that the male-dominated profession was recommended more to the male consumer compared to the female consumer when controlling for the perceived gender-dominance of the certificate program, p = .003.